(3GJSGe GdKZhQs - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3hHYO agPG JYdjb SejJg GHJSGe GdKZhQ Yf eG bjd ai faY GdRghQ hgh eQJH Ydi MQha GdeYLe bGd GHh MfjaI abGMg THjg HfhQ GdfQLS GdG Gfg GdWa efg s
(3BNQgG (B:s
(3hbGd GdTQja Gf GNP RgQI hSMb hTQH ef eGFg KdGKI GjGe ai cd jhe ebOGQkG hajg bWY fRa GdGRgGQ hdjS jfJaY HTF ef GdjGSejf HZjQ RgQ s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdRQGYI h GdCYTGHs